2022
DOI: 10.1055/a-1716-1856
|View full text |Cite
|
Sign up to set email alerts
|

Serious Adverse Drug Reactions in Children and Adolescents Treated On- and Off-Label with Antidepressants and Antipsychotics in Clinical Practice

Abstract: Introduction Despite the growing evidence base for psychotropic drug treatment in pediatric patients, knowledge about the benefit-risk ratio in clinical practice remains limited. The ‘Therapeutic Drug Monitoring (TDM)-VIGIL’ study aimed to evaluate serious adverse drug reactions (ADRs) in children and adolescents treated with antidepressants and/or antipsychotics in approved (‘on-label’), and off-label use in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
2
16
0
1
Order By: Relevance
“…Up to now, depression has become the third largest burden disease in the world, and the number of suicides caused by depression has reached 1 million every year [ 3 ]. Conventional antidepressants, typically selective serotonin reuptake inhibitors (SSRIs), have limitations in long lag period, nonresponsive subpopulations, and adverse effects [ 4 6 ]. Therefore, it is of great significance to find new antidepressant drugs with more rapid, effective, economical, and safe antidepressant treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, depression has become the third largest burden disease in the world, and the number of suicides caused by depression has reached 1 million every year [ 3 ]. Conventional antidepressants, typically selective serotonin reuptake inhibitors (SSRIs), have limitations in long lag period, nonresponsive subpopulations, and adverse effects [ 4 6 ]. Therefore, it is of great significance to find new antidepressant drugs with more rapid, effective, economical, and safe antidepressant treatment.…”
Section: Introductionmentioning
confidence: 99%
“…EPS and QTc prolongation were the most frequently observed sADRs. Interestingly, in the TDM Vigil study 25 , psychiatric (not somatic) sADRs were most frequently reported. In our sample, psychiatric sADRs were very rare.…”
Section: Discussionmentioning
confidence: 99%
“…The reference study for estimating the frequency of sADR was the TDM-VIGIL study with 8.3% sADR (Egberts et al 2022 ). An estimated sample size of 1600 electronic medical records of hospitalized patients was provided, with approximately half of the patients having at least 1 psychotropic medication documented during the inpatient stay.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, children and adolescents with mental disorders are at higher or unknown risk for serious adverse drug reactions (sADRs) (Gerlach and Warnke 2016 ). sADRs in children and adolescents treated with psychotropic drugs have been reported in clinical trials (Nor Aripin et al 2012 ) and everyday clinical practice (Aagaard et al 2010 ; Egberts et al 2022 ) and can have far-reaching consequences. There is an urgent need for a strict risk–benefit assessment and careful patient and drug monitoring (Egberts et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%